2022
DOI: 10.24114/kjb.v11i3.38827
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Media Film Animasi Terhadap Kemampuan Menulis Teks Narasi Siswa Kelas VII Smp Negeri 2 Galesong Selatan Kabupaten Takalar

Abstract: Penelitian ini bertujuan untuk mendeskripsikan pengaruh penggunaan media film animasi terhadap kemampuan menulis teks narasi siswa kelas VII SMP Negeri 2 Galesong Selatan Kabupaten Takalar. Metode penelitian ini adalah penelitian kuantitatif dengan jenis penelitian experiment dengan desain pretest-posttest control group desain. Perbedaan ketarmpilan menulis teks narasi antara kelas eksperimen dan kelas kontrol ditunjukkan dengan hasil uji analisis atatistik Wilcoxon dan Mann Whitney. Hasil uji analisis statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…However, in reality, there are still several issues in students' narrative writing skills. Previous research conducted by other researchers has found some problems, such as students' low talent in narrative writing, which impacts their ability to write narratives (Sulaiman et al, 2022). Additionally, students tend to find Indonesian language learning boring, and writing narratives is considered a challenging task (Deminda, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, in reality, there are still several issues in students' narrative writing skills. Previous research conducted by other researchers has found some problems, such as students' low talent in narrative writing, which impacts their ability to write narratives (Sulaiman et al, 2022). Additionally, students tend to find Indonesian language learning boring, and writing narratives is considered a challenging task (Deminda, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Once the importance of the Indonesian language subject in schools, it is necessary to pay attention to the success of students learning in language and communicating in schools because learning success is the most expected thing in the process and implementation of education in schools (Magdalena et al, 2021). However, in reality there are still some problems in writing narrative skills for students, these problems are based on previous studies conducted by other researchers, such as the low talent that students have in writing narratives so that it has an impact on students' skills in writing narratives (Sulaiman et al, 2022). Then students still think learning Indonesian is boring learning and writing narratives is learning that is difficult to do (Deminda, 2022), as well as a lack of imagination, memory and Open Access: https://ejournal.papanda.org/index.php/edukasiana/ the ability to compose words in students' narrative writing skills (Wahyuningtiyas & Rukmi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Begitu pentingnya mata pelajaran Bahasa Indonesia di dalam sekolah, maka keberhasilan belajar peserta didik dalam berbahasa dan berkomunikasi didalam sekolah perlu diperhatikan karena keberhasilan belajar merupakan hal yang paling diharapkan dalam proses dan pelaksanaan pendidikan di dalam sekolah (Magdalena et al, 2021). Namun pada kenyataannya masih ditemukanya beberapa permasalahan dalam keterampilan menulis narasi bagi siswa, permasalahan ini berdasarkan penelitian-penelitian sebelumnya yang dilakukan oleh peneliti lainya, seperti rendahnya bakat yang dimiliki siswa dalam menulis narasi sehingga berdampak pada kecakapan siswa dalam menulis narasi (Sulaiman et al, 2022). Kemudian siswa masih menganggap pembelajaran Bahasa Indonesia merupakan pembelajaran yang membosankan dan menulis narasi merupakan pembelajaran yang sulit untuk dilakukan (Deminda, 2022), serta kurangnya imajinasi, daya ingat dan kemampuan merangkai kata pada siswa dalam keterampilan menulis narasi (Wahyuningtiyas & Rukmi, 2018).…”
unclassified